Cover Image. Issue 3 (13th August 2018) - Diaz, Candido; Tanikawa, Akio; Miyashita, Tadashi; Dhinojwala, Ali; Blackledge, Todd A.
Abstract : ON THE COVER: The cover image, by Candido Diaz et al., is based on the Research Article Silk structure rather than tensile mechanics explains web performance in the moth‐specialized spider, Cyrtarachne, DOI:10.1002/jez.2212 . Photo Credit: Sarah Han.